Memristor and Trivium-based true random number generator - Kaya, Turgay (Elsevier, 2020)
Random numbers are critical in encryption. In this article, a memristor and Triviumbased structure has been proposed to generate true random numbers. The memristor, which is a complementary element between the flux and charge, was used as a noise source. The raw data obtained from the memristor having chaotic behavior were normalized and given as a key to Trivium. Trivium algorithm, which is widely used in the literature, was used to eliminate the correlation between the numbers produced. NIST SP 800-22 tests were used for the statistical analysis of the numbers obtained from the output of Trivium. In addition, the scale index test was used to observe the nonperiodic behavior of the memristor. The results show that the random numbers generated can be used in many areas. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Memristor; Chaos; Trivium; True random number generator; Statistical test